Diversity of endophytic yeast in different varieties of waxy sorghum at flowering period - LIU Wenwen, CHEN Lu, HU Lianqing, FENG Ruizhang, WEI Qin, ZHOU Wanhai, XIANG Qiujin, HUANG Siqi (Zhongguo niangzao)
The diversity of endophytic yeast in different varieties and organs of waxy sorghum was analyzed using Illumina MiSeq high-throughput sequencing technology at flowering period, and the differential and functional flora were also analyzed using linear discriminant analysis effect size (LEfSe) and FUNGuild, respectively. The results showed that a total of 182 genera in 8 phyla were annotated. The community diversity and richness of endophytic yeast in Qingkeyang were higher than that of Jinnuoliang 1, and the richness of leaf was the highest. Ascomycota was the dominant phylum in different varieties and the stems and leaves. Basidiomycota was the dominant phylum in flowers, and the dominant phylum in roots was unclassified fungi. At the genus level, the dominant genera in Jinnuoliang 1 and Qingkeyang were unclassified Chaetothyriales and unclassified fungi, respectively. The dominant genera of the roots, stems, leaves and flowers were unclassified fungi, Ramichloridium, unclassified Chaetothyriales and Didymium, respectively. LEfSe analysis showed that the most important difference indicator genus was Papiliotrema. The most important differential indicator genera for roots, stems, leaves and flowers were Fusarium, Ramichloridium, Alatosessilispora and Pseudozyma, respectively. FUNGuild functional prediction showed that waxy sorghum flora has rich functions and was divided into 7 nutritional models and 24 ecological functional groups. Qingkeyang and the leaves had the greatest numbers of unique functional fungus.